Two modes of LyC escape from bursty star formation: implications for [C ii] deficits and the sources of reionization. Issue 1 (21st October 2022) - Katz, Harley; Saxena, Aayush; Rosdahl, Joki; Kimm, Taysun; Blaizot, Jeremy; Garel, Thibault; Michel-Dansac, Leo; Haehnelt, Martin; Ellis, Richard S; Penterrici, Laura; Devriendt, Julien; Slyz, Adrianne
ABSTRACT: We use the SPHINX 20 cosmological radiation hydrodynamics simulation to study how Lyman continuum (LyC) photons escape from galaxies and the observational signatures of this escape. We define two classes of LyC leaker: Bursty Leakers and Remnant Leakers, based on their star formation rates (SFRs) that are averaged over 10 Myr (SFR10 ) or 100 Myr (SFR100 ). Both have f_esc20 per cent and experienced an extreme burst of star formation, but Bursty Leakers have SFR10 > SFR100, while Remnant Leakers have SFR10 < SFR100 . The maximum SFRs in these bursts were typically ∼100 times greater than the SFR of the galaxy prior to the burst, a rare 2σ outlier among the general high-redshift galaxy population. Bursty Leakers are qualitatively similar to ionization-bounded nebulae with holes, exhibiting high ionization parameters and typical H ii region gas densities. Remnant Leakers show properties of density-bounded nebulae, having normal ionization parameters but much lower H ii region densities. Both types of leaker exhibit [C ii ]158μm deficits on the [C ii ]–SFR100 relation, while only Bursty Leakers show deficits when SFR10 is used. We predict that [C ii ] luminosity and SFR indicators such as H α and M_1500A can be combined to identify both types of LyC leaker and the mode by which photons are escaping. These predictions can be tested with [C ii ] observations of known z = 3–4 LyC leakers. Finally, we show that leakers with f_esc20 per cent dominate the ionizing photon budget at z ≳ 7.5 but the contribution from galaxies with f_esc5 per cent becomes significant at the tail-end of reionization.